Going beyond 30 seconds management and culture in the television commercial production process - Yu, Faye Ananda Cruz 1991- (University of the Philippines Diliman, 2013)
"This study aims to explain the phenomenon of television commercial production in the Philippine by describing the processes involved then giving meaning to these processes. In order to do that, the management and culture aspects of TVC production were examined. For management, the framework that was used was Rodriguez and Echanis' "The Five Fundamentals of Management" (1997) which are: planning, organizing, stafing, directing, and control. For culture, Felipe Jocano's concept of the Filipino corporate culture was employed. These were applied to four case studies of productions from one of the country's top production houses, Unitel. Following the five fundamentals framework, key themes were identified in these cases and were compared with the standards set by Rodriguez and Echanis. Through this, the points of what constitutes an effective television commercial were also identified. One of these points was the impact that Filipino culture has on management. This thesis can be considered as a manual on how to produce effective television commercials in the Philippines."